Contribution towards the knowledge of Rhinotragini (Coleoptera, Cerambycidae). V. Reconsideration of Rhopalessa rubroscutellaris (Tippmann, 1960) - Clarke, Robin O.S.; Martins, Ubirajara R.; Santos-Silva, Antonio (Papéis Avulsos de Zoologia, 2012)
Corrections to the revision of Rhopalessa Bates, 1873 (Clarke et al. 2011), with the transfer of two species to a new genus, Rashelapso: R. durantoni (Peñaherrera-Leiva & Tavakilian, 2004) comb. nov., and R. schmidi sp. nov. (previously considered to be conspecific with Ommata (Rhopalessa) rubroscutellaris Tippmann, 1960 by the authors). Ommata (Rhopalessa) rubroscutellaris is now considered a junior synonym of Laedorcari fulvicollis (Lacordaire, 1868).